Fenomena Penghindaran Pembayaran PPN yang Sudah Dipungut oleh Pengusaha Kena Pajak, Apa Motifnya? - Sirait, Bernard; Nupus, Via Aviatun; Meilena, Wanda Rika; Ratnasari, Nugi; Arifin, Muhammad Jaenal; Mulyadi, Roza (JURNAL AKUNTANSI DAN MANAJEMEN, 2024)
This research aims to determine the phenomenon of evasion of payment of value added tax which has been collected by taxable entrepreneurs in Indonesia. The focus of this research was carried out at the Cilegon Pratama Tax Service Office by gathering information from Account Representatives and taxpayers. The matter studied is related to the motives that cause taxpayers to avoid paying value added tax that has been levied on the delivery of taxable goods and/or taxable services. In 2023, the realization of tax revenue from the Cilegon Pratama Tax Service Office reached 110.13%, however this was not supported by revenue from value added tax which only reached 94.18%. This indicates that there is avoidance of paying value added tax which has been collected by taxable entrepreneurs. Using a transcendental phenomenological approach, this research explores the motives that encourage taxable entrepreneurs to avoid paying the value added tax that has been collected without depositing it into the state treasury. The results of the research show that taxpayers are aware that evasion of payment of value added tax that has been collected is an unlawful act that can be subject to sanctions in the form of fines or criminal penalties, however, late payment of bills from transaction counterparties and liquidity difficulties are the main motives for taxpayers not to deposit VAT into the state treasury.